STRATEGI KOMPETITIF DAN KOLABORATIF DALAM MUNCULNYA INDUSTRI: TEORI DAN PRAKTIK DALAM MANAJEMEN STRATEGIS KONTEMPORER - Darlia, Nelvika; Mustofa, Amirul; Yunus, Eddy (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This article discusses the application of competitive strategy and collaborative strategy in the emergence of new industries in Indonesia, focusing on two key sectors: fintech and renewable energy. In the fintech industry, companies such as GoPay, OVO, and DANA use competitive strategies to gain an advantage through product differentiation and cost efficiency. On the other hand, in the renewable energy industry, collaborative strategies involving partnerships between companies, the government, and research institutions play a crucial role in overcoming infrastructure and financing challenges. This article demonstrates that although these two strategies are often viewed as separate approaches, they complement each other and are key in creating a growing industrial ecosystem. Based on this analysis, it is recommended that companies in Indonesia integrate both strategies to foster sustainability and growth in emerging industries.